Feminist postcolonial theory : a reader - Lewis, Reina, 1963-; Mills, Sara, 1954- (Edinburgh University Press, 2003)
The readings have been selected to examine the textual and discursive nature of colonial and post-colonial discourse in relation to gender and the material effects of the post-colonial condition and practices developed in relation to it.
Keywords: Feminist theory -- History.; Feminism -- History.; Postcolonialism.; Théorie féministe -- Histoire.; Féminisme -- Histoire.; Postcolonialisme.; postcolonialism.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Feminism; Feminist theory; Postcolonialism; Feminismus; Postkolonialismus; Feminisme.; Postkolonialisme.; Theorie.; Aufsatzsammlung.; History